2005
DOI: 10.1161/01.str.0000149631.52985.27
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors in Spontaneous Cervical Artery Dissections

Abstract: Background and Purpose-Observations in patients with arterial aneurysms, fibromuscular dysplasia, and spontaneous cervical artery dissection (sCAD) indicate that protease inhibitor deficiency might boost the enzymatic destruction of arterial tissue and increase the risk of these arterial wall diseases. Here we present the first large investigation of the protease inhibitor hypothesis in patients with sCAD. Methods-Eighty patients with sCAD were compared with 80 age-and sex-matched healthy individuals. ␣ 1 -ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…␣ 1 -AT One small study (nϭ22 cases) found low levels of ␣ 1 -AT to be strongly associated with CAD (OR adj , 17.7; 95% CI, 2.9 to 105.6), 14 which is in contrast with a much larger study (nϭ80 cases), 38 as well as the study by Grau et al 12 Selection bias, small sample size, and lack of description of the study population were the main methodological shortcomings in the study by Vila et al, 14 whereas Konrad et al used a robust sample size and a population-based control group. 38 Additionally, Konrad et al 38 found that the ␣ 1 -AT genotypes did not differ among cases and controls, as did Grond-Ginsbach et al 35 Connective Tissue Disease Three studies were identified from the same research group, with the same subjects being included in subsequent larger studies.…”
Section: Genetic or Inborn Predisposition/disorders With A Familial Amentioning
confidence: 81%
See 2 more Smart Citations
“…␣ 1 -AT One small study (nϭ22 cases) found low levels of ␣ 1 -AT to be strongly associated with CAD (OR adj , 17.7; 95% CI, 2.9 to 105.6), 14 which is in contrast with a much larger study (nϭ80 cases), 38 as well as the study by Grau et al 12 Selection bias, small sample size, and lack of description of the study population were the main methodological shortcomings in the study by Vila et al, 14 whereas Konrad et al used a robust sample size and a population-based control group. 38 Additionally, Konrad et al 38 found that the ␣ 1 -AT genotypes did not differ among cases and controls, as did Grond-Ginsbach et al 35 Connective Tissue Disease Three studies were identified from the same research group, with the same subjects being included in subsequent larger studies.…”
Section: Genetic or Inborn Predisposition/disorders With A Familial Amentioning
confidence: 81%
“…29,40 Of the remaining studies, conflicting results were found for ␣ 1 -AT. 12,14,38 The methodologically stronger study by Konrad et ‡References 3, 4, 9, 10, 12-14, 27-31, 37, 38, 40, 44, 46, 47 al 38 suggested that proteinase inhibitor levels are not important in CAD. Additionally, 2 studies of homocysteine based their results on a rather small sample size, 9,10 as did the studies of vessel abnormalities 28,30,45 (cases, range: Nϭ25 to 32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although low AAT plasma levels were found in a small case control study of 22 Spanish patients diagnosed with spontaneous cervical artery dissection [40], other larger case control studies did not support this relationship [39], or a relationship between α2-macroglobulin levels or ATT genotypes and spontaneous cervical artery dissection [41].…”
Section: Risk Factorsmentioning
confidence: 87%
“…A recent case-control study found that hypertension was also significantly associated with sCAD and cerebral infarction [27]; Konrad and colleagues also found smoking and hypertension to be associated with dissection [28]. In another study, the presence of hypertension was associated with a lack of recanalization [29].…”
Section: Vascular Risk Factorsmentioning
confidence: 99%